Demographic and socioeconomic inequalities in the risk of emergency hospital admission for violence: cross-sectional analysis of a national database in Wales. Issue 8 (24th August 2016) - Long, Sara Jayne; Fone, David; Gartner, Andrea; Bellis, Mark A
Abstract : Objectives: To investigate the risk of emergency hospital admissions for violence (EHAV) associated with demographic and socioeconomic factors in Wales between 2007/2008 and 2013/2014, and to describe the site of injury causing admission. Design: Database analysis of 7 years' hospital admissions using the Patient Episode Database for Wales (PEDW). Setting and participants: Wales, UK, successive annual populations ∼2.8 million aged 0–74 years. Primary outcome: The first emergency admission for violence in each year of the study, defined by the International Classification of Diseases V.10 (ICD-10) codes for assaults (X85-X99, Y00-Y09) in any coding position. Results: A total of 11 033 admissions for assault. The majority of admissions resulted from head injuries. The overall crude admission rate declined over the study period, from 69.9 per 100 000 to 43.2 per 100 000, with the largest decrease in the most deprived quintile of deprivation. A generalised linear count model with a negative binomial log link, adjusted for year, age group, gender, deprivation quintile and settlement type, showed the relative risk was highest in age group 18–19 years (RR=6.75, 95% CI 5.88 to 7.75) compared with the reference category aged 10–14 years. The risk decreased with age after 25 years. Risk of admission was substantially higher in males (RR=4.55, 95% CI 4.31 to 4.81), for residents of the most deprived areas of Wales (RR=3.60, 95% CI 3.32 to 3.90) compared with the least deprived, and higher in cities (RR=1.37, 95% CI 1.27 to 1.49) and towns (RR=1.32, 95% CI 1.21 to 1.45) compared with villages. Conclusions: Despite identifying a narrowing in the gap between prevalence of violence in richer and poorer communities, violence remains strongly associated with young men living in areas of socioeconomic deprivation. There is potential for a greater reduction, given that violence is mostly preventable. Recommendations for reducing inequalities in the risk of admission for violence are discussed.